PELAYANAN TERPADU SURAT IZIN USAHA PERDAGANGAN DI KABUPATEN KUBU RAYA - Daniel Lentasi Sindang E.21110087 (FISIP Universitas Tanjungpura, 2012)
AbstractThe purposed of this article is intended to determine the implementation of licensing services ofthe Board of Investment and Integrated Services (BPMPT) Kubu Raya Regency. The focusedproblem of this article is many owners who did not have business license trade (Business License)in terms of license are also a prerequisite for the operation of a business. The benefits of this articleis to ensure that the officers’ services could be achieved by following the process set out inRegents regulation Number. 22 Year 2011. A reviewed of the services’ process on simplicity,clarity and timeliness is very good. Based on the above it is suggested that the simplicity, clarityand timeliness can be improved. .Keywords: Integrated Services, Simplicity Processes, Procedures Clarity and certainty of time.